Effect of tillage intensity, fertilizer and manure on root mass density, soil properties and their correlation on rice (Oryza sativa L.) yield (Bangladesh Journal of Agricultural Research, 2012)
An experiment was carried out at the Bangladesh Agricultural University Farm, Mymensingh during the Aman season of 2008 to study the effect of tillage intensity, fertilizer and manure on the root mass density soil properties and their correlation on rice yield (BRRI dhan 41). The experiment was laid out in a split plot design with three replications. The treatments were three tillage operations as factor A: one passing (P1), two passing (P2), and three passing (P3) of a power tiller and four fertilizer and manure treatments as factor B: recommended dose of fertilizers (FM0), 50% of N plus rest of recommended dose of fertilizers + cowdung @ 5 t/ha (FM1), 50% of N plus rest of recommended dose of fertilizers + rice straw @ 5 t/ha (FM2) and 50% of N plus rest of recommended dose of fertilizer + cowdung @ 2.5 t/ha plus rice straw @ 2.5 t/ha (FM3). The highest and the lowest bulk densities were found in P1FM0 and P3FM treatments, respectively. The maximum soil moisture content and air filled porosity were obtained in P3FM1 treatment, whereas PM1FM0 demonstrated the lowest soil moisture content. The maximum (8.09 mg cm-3) and minimum (1.63 mg cm-3) root mass densities were observed in P3 (10 cm depth) and P1 (10-20 cm depth) treatments, respectively. The highest grain yield was recorded in P3FM0 treatment. Root mass density was positively correlated with soil moisture content and grain yield, but negatively with bulk density. Bangladesh J. Agril. Res. 37(3): 529-535, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12129